Autumn weight of female bears - Hertel, Anne G.; Bischof, Richard; Langvall, Ola; Mysterud, Atle; Kindberg, Jonas; Swenson, Jon E.; Zedrosser, Andreas (Dryad Digital Repository, 2017)
Bodyweight of female brown bears (Ursus arctos) shot in the annual bear hunting season in autumn 2006 - 2015.